(untitled) (Research, Society and Development, 2022)
Process optimization is essential for the large-scale viability of the food industry. Central composite rotational design (CCRD) followed by response surface analysis was used to optimize the production of fish protein hydrolysate (FHP). FHP was obtained from tilapia filet trimmings hydrolyzed subjected using Alcalase 2.4L™, Neutrase™, and Novo-Pro™ D enzymes under temperature, enzyme concentration, and pH-controlled conditions. A 23-3 full factorial design (FFD) was initially employed to select the most influential variables in the process (with each enzyme used in the CCRD). From the FFD, temperature and enzyme concentration for Alcalase 2.4L™ and Novo-Pro™ D, and temperature and pH for Neutrase™ were selected. The estimated maximum degree of hydrolysis (DHmax) using Alcalase 2.4L™ was 60.05% during 180 min of processing at 39.03°C and 0.65% enzyme concentration. A DHmax of 56.96% was reached using Neutrase™ during 120 min at 39.46°C and 6.039 pH. Novo-Pro™ D was associated with a DHmax of 54.76% during 60 min at 47.95°C and 0.866% enzyme concentration. The three enzymes showed promising results for obtaining FHP with high DH from Nile tilapia filet trimmings.